A practical note on transferring ideas and methods from consultancy practice to the MPA classroom: A personal account from a Danish case study. (March 2016) - Ry Nielsen, JC; Quinn, Brid
At the lead author's home institution – Copenhagen Business School (CBS) – the combination of theory and practice is seen as very important in teaching. Research-based teaching is the slogan. In this respect, CBS has the same ambition as other universities. But it seems as if CBS has an advantage at the master's level, because students come with a lot of experience. The average age of the MPA students is generally over 40. Consequently, they are able to bring practice into the classroom and to confront it with theories and also the experiences of their fellow students. There are, however other ways of bringing practice and theory together. In this note, the author reviews a three-year consultancy/research project in a merging hospital department. The aim of the note is twofold. One is to detail the more exploratory methods used to develop the organization. The second is to evaluate whether these methods can be transferred to a potential MPA module at CBS. It is concluded that for some of the methods such as diary-keeping and agenda-setting, transfer is easy. Other methods, such as using a cross-sectional group or manager role-analysis, may not transfer easily but could be applied in the home organizations of participants. The design of the module and the non-traditional roles of the teachers are very important for successful implementation.